Factors influencing the Bangladeshi consumers’ purchase decision regarding fast moving consumer goods: an exploratory study - Ullah, G. M. Shafayet; Prince, Panuel Rozario (© 2012 The IUP Journal of Brand Management, 2016)
This article was published in The IUP Journal of Brand Management [© 2012 The IUP Journal of Brand Management] and the definite version is available at : http://eds.a.ebscohost.com/eds/pdfviewer/pdfviewer?sid=63840fd4-1c0c-4223-a43d-47dc00a149c9%40sessionmgr4008&vid=2&hid=4205 The article website is at: http://www.iupindia.in/1203/Brand%20Management/Factors_Influencing_the_Bangladeshi_Consumers.html